A Study of Performance Management System With Special Reference to Its Industry Across The Globe: Research Article - Nigam, Nimesh (Journal of Advanced Research in Entrepreneurship, Innovation and SME Management, 2020)
Management systems enable you to track and monitor the performance of individual employees, departments, and the organization overall. These systems are often based on organizational and job specific competencies which need to be obtained for successful job performance.